2004
DOI: 10.1002/mabi.200400075
|View full text |Cite
|
Sign up to set email alerts
|

Mutation Effects of a Conserved Alanine (Ala510) in Type I Polyhydroxyalkanoate Synthase from Ralstonia eutropha on Polyester Biosynthesis

Abstract: Type I polyhydroxyalkanoate (PHA) synthases, as represented by Ralstonia eutropha enzyme (PhaC(Re)), have narrow substrate specificity toward (R)-3-hydroxyacyl-coenzyme A with acyl chain length of C3-C5 to yield PHA polyesters. In this study, saturation point mutagenesis of a highly conserved alanine at position 510 (A510) in PhaC(Re) was carried out to investigate the effects on the polymerization activity and the substrate specificity for in vivo PHA biosynthesis in bacterial cells. A series of saturation mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
28
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 31 publications
2
28
0
2
Order By: Relevance
“…A G4D or F420S mutation results in more PHB accumulation in recombinant E. coli (26,41). Another beneficial mutation, A510D(E), leads PhaC H16 to synthesize a higher-molecular-weight polymer (43). The thermostability of PHA synthase has never been the aim of protein engineering.…”
mentioning
confidence: 99%
“…A G4D or F420S mutation results in more PHB accumulation in recombinant E. coli (26,41). Another beneficial mutation, A510D(E), leads PhaC H16 to synthesize a higher-molecular-weight polymer (43). The thermostability of PHA synthase has never been the aim of protein engineering.…”
mentioning
confidence: 99%
“…Substitution with uncharged residues (G/M/S/T/Q) was concluded to be best for enhancement of both PHA accumulation and 3HHx fraction. Interestingly, it was found that A510M/Q in PhaC Re also improved PHA accumulation and 3HHx fraction in the resultant copolymer (12).…”
Section: Discussionmentioning
confidence: 99%
“…1) located at position 479 in PhaC Cs . Functional implications of amino acid substitutions at the position based on previous studies include alterations in substrate specificity, and in certain cases, variations in the molecular weight of the resultant polymer were observed (10,12,23). Position 479 in PhaC Cs , therefore, appears to be a suitable candidate for the mutagenesis approach in order to achieve similar positive effects.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…3,14) It has been reported that R. eutropha PHB À 4 expressing Aeromonas caviae PHA synthase (PhaC Ac ), which belongs to class I synthases but has exceptionally broad substrate specificity, syn- Fig. 1.…”
Section: )mentioning
confidence: 99%